Observations and simulations of midlatitude ionospheric and thermospheric response to the January 2013 stratospheric sudden warming event. Issue 9 (16th September 2016) - Wu, Qian; Maute, A.; Yudin, V.; Goncharenko, L.; Noto, J.; Kerr, R.; Jacobi, Christoph
Abstract: Using observations from midlatitudes, we examine the ionospheric and thermospheric responses to the 2013 stratospheric sudden warming event by comparing data with four simulations performed by the Whole Atmosphere Community Climate Model eXtended (WACCM‐X), Thermosphere‐Ionosphere Mesosphere Electrodynamics General Circulation Model (TIMEGCM), and Thermosphere‐Ionosphere Electrodynamics General Circulation Model (TIEGCM). The WACCM‐X simulation was nudged by the GEOS‐5 data. The two TIMEGCM simulations were nudged by the Modern‐Era Retrospective analysis for Research and Applications data and by the aforementioned WACCM‐X outputs, respectively. The standard TIEGCM simulation was also performed. These four simulations were compared with Millstone Hill (42.6°N, 71.4°W) incoherent scatter radar data, Millstone Hill and Boulder (40.1°N, 105.2°W) upper and lower thermospheric wind data. The meteor radar data from Collm (51.3°N, 13°E) were also used to examine the zonal wave number of the semidiurnal tide (SD). We evaluate the model simulations of the mesospheric and thermospheric responses to the 2013 SSW. The TIMEGCM simulation nudged with the WACCM‐X output has suitable stratospheric input and ionospheric dynamics and can reproduce a sharp rise of hm f 2 on January 12 observed by the Millstone Hill radar. The comparison of different models with the lower thermospheric SD tide yielded mixed results. The SD tide maintained mostly as a migrating tide for most of the time and matched the TIEGCM simulation very well. The WACCM‐X appeared to perform better when the observed SD tide displays the large phase shift. It also has larger and more variable SD tide amplitude. The two TIMEGCM simulations have smaller SD amplitudes in general. Observations showed complex SD tide patterns after 20 January, which was difficult to characterize as a migrating tidal mode. Key Points: Right stratospheric input is a key for modeling the stratospheric sudden warming The TIMEGCM nudged with the WACCM‐X reproduces strong equatorward thermospheric winds and its ionospheric effects The simulations still cannot fully capture the variation in the semidiurnal tide during the 2013 SSW event